Olympiads in Informatics: Macedonian Experience, Needs, Challenges - Jancheski, Metodija; Pacovski, Veno (My University, 2007)
The introductory part of the paper includes the brief description of the current Macedonian educational system, including information about national ICT policy, primary and secondary education curricula, technological equipment, the level of using ICT in education, and projects related with ICT. Presently, there is enforced computerization of our country (an enormous increase in numbers of computers in primary and secondary schools, free education for computer illiterate and efforts are made for full computerization of every aspect of the society). This paper is about national informatics competitions in Macedonia for secondary school students, their organization, and scope. Computer Society of Macedonia (CSM) is the organizer of National competitions. The regular activities of CSM also include: organization and execution of seminars for permanent education of IT teachers in secondary and elementary schools, and there are efforts made to influence national education of IT. CSM organizes four levels of state annual competitions with two groups of original problems. The top ranked four contestants at the Olympiad represent Macedonia at the international competitions: BOI and IOI.
Keywords: education, competition, programming, computerization, olympiad in informatics, Macedonia